Proposal for a new protein therapeutic immunogenicity titer assay cutpoint. (December 2011) - Wakshull, Eric; Hendricks, Robert; Amaya, Caroline; Coleman, Daniel
Background: Generally, immunogenicity assessment strategies follow this assay triage schema: screen→confirm→titer. Each requires the determination of a threshold value (cutpoint) for decision making. No guidance documents exist for the determination of a specific titration assay cutpoint. The default practice is to use the screening assay cutpoint, frequently leading to controls or samples not reaching this cutpoint. We propose a method for determination of a titration cutpoint based upon the variance of the negative-control sample.Results: Positive-control samples that did not cross a screening cutpoint did cross the titer cutpoint, albeit generating slightly lower titer values.Conclusion: Our approach is consistent with the statistical methods currently recommended for the screening and confirmatory assay cutpoints and is operationally simple and efficient.